(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Abstract—The rapid growth of cellular communication technology necessitates fast and stable internet connections. This research addresses the limited studies on 5G network performance in Surakarta City, which is experiencing increased demand for reliable internet access. We employed a drive test method using the G-Net Track Pro application to measure 5G signal quality based on RSRP, RSRQ, and SINR parameters on 2100 MHz and 2300 MHz frequencies. The study aimed to compare signal quality between Telkomsel and XL across four key locations in Surakarta. Results indicate that Telkomsel generally shows excellent RSRP, while XL also provides competitive signal strength in specific areas. RSRQ for both operators consistently falls into the "Good" category. However, SINR values varied significantly, highlighting the impact of interference and noise on overall user experience, particularly in Jl. Kebangkitan Nasional for Telkomsel and Jl. Ronggowarsito for XL. This study emphasizes the importance of comprehensive signal parameter measurements for real-time network assessment.